The Use of “Characteristics of Living Things” Song Media and Gamification in Improving Third-Grade Students’ Learning Outcomes on the Characteristics of Living Things Material - Anang Fathoni; Amandariella Samahita Prasetyo; Tri Makno Hartanto (PT. Lontara Digitech Indonesia, 2026)
Natural and Social Sciences (IPAS) is one of the subjects that plays an important role in developing students’ understanding of basic science concepts and the surrounding environment. However, in practice, many students still experience difficulties in understanding the material because IPAS is new material for third-grade students with many new terms in it. This study aims to improve the learning outcomes of third-grade students at SD Negeri Pasarbatang 01 on the material of the characteristics of living things through the application of the “Characteristics of Living Things” song media integrated with gamification. This type of research is Classroom Action Research (CAR) with 20 third-grade students as the subjects. Data were collected through learning outcome tests and analyzed using descriptive statistics. The results showed an increase in learning outcomes in each cycle. The average learning outcome score in the pre-cycle was 60.05 with 30% mastery, increased in Cycle I to 67.25 with 50% mastery, and increased again in Cycle II to 75.25 with 60% mastery. These results prove that the use of song media combined with gamification is able to create more enjoyable, interactive, and effective learning, thereby improving students’ learning outcomes in IPAS subjects in elementary school.